Formation of Orthogonal Components of Input Signals in Digital Measuring Protection Elements with Correction of Dynamic Errors - F. A. Romaniuk; Yu. V. Rumiantsev; V. Yu. Rumiantsev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2022)
Digital measuring elements in microprocessor protections of electrical installations are implemented mainly with the use of orthogonal components of input signals. To form orthogonal components in microprocessor protections, digital Fourier filters are most widely used, the action of which is al-ways inertial in transient modes. As a result, a dynamic error appears, changing over time and completely disappearing when a steady-state regime occurs. The dynamic error consists of amplitude and phase errors, which can significantly affect the functioning of digital measuring elements and create conditions for their excessive triggering during external short circuits and deceleration of triggering during internal short circuits. Therefore, it is advisable to compensate for the dynamic error, for which it is proposed to determine the amplitude and phase of the fundamental harmonic signal by specially formed orthogonal components. The proposed method of forming orthogonal components of the signal with compensation of dynamic amplitude and phase errors is based on the use of orthogonal components of the digital Fourier filter, followed by the determination of their samples of the final orthogonal components that coincide with the orthogonal components of Fourier in steady-state mode and shifted in phase relative to the latter in transient mode. The amplitude and phase of the signal with minimal dynamic phase errors are calculated from the samples of the final orthogonal components in the digital measuring element. In the dynamic modeling environment of MATLAB-Simulink-SimPowerSystems, a digital model is implemented, which includes a power system, a three-phase group of current transformers, a load, a short-circuit block, as well as a model of a digital measuring element implemented on the basis of the final orthogonal components. The operation of the digital model was checked using two types of test effects, viz. a sinusoidal signal with a frequency of 50 Hz, and a signal close to the real secondary current of a short-circuit current transformer. As a result of the calculations, it was found that digital measuring elements made on the basis of the proposed methodology made it possible to reduce the relative dynamic amplitude and phase errors by three to four times, as compared with the Fourier measuring element taken as a reference.